Algorithmic trading and corporate investments - Kopita, Anastasia; Bilinski, Pawel; Panayides, Marios; Karamanou, Irene (My University, 2023)
Using the Tick Size Pilot experiment as an exogenous shock to algorithmic trading (AT), we document that a reduction in AT has a negative causal effect on corporate investments. This result reflects lower speed of price discovery and the extent to which stock prices capture signals about the value of new investments. Consistently, we report slower price responses to firms’ disclosure of investment signals in stocks that experienced a reduction in AT, which leads to stock underpricing and reduces managerial incentives to pursue new investments. The effect we document is not explained by changes in stock liquidity, institutional ownership, firm monitoring, financial constraints, or in the quality of the firm’s information environment that can correlate with the tick size increase.
Keywords: Algorithmic trading; Corporate investments